2000
DOI: 10.1071/pp00001
|View full text |Cite
|
Sign up to set email alerts
|

Regulation and function of extracellular invertase from higher plants in relation to assimilate partitioning, stress responses and sugar signalling

Abstract: This paper originates from a presentation at the International Conference on Assimilate Transport and Partitioning, Newcastle, NSW, August 1999 Carbohydrates are synthesised in photosynthetically active source tissues and exported, in most species in the form of sucrose, to photosynthetically less active or inactive sink tissues. Sucrose hydrolysis at the site of utilisation contributes to phloem unloading. This phenomenon links sink metabolism with phloem transport to, and partitioning between, sinks. Inverta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
37
0
2

Year Published

2001
2001
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(40 citation statements)
references
References 54 publications
1
37
0
2
Order By: Relevance
“…This study strongly supports the importance of apoplastic cleavage of sucrose by extracellular invertase for supplying carbohydrates to sink tissues and for normal development of plants, which has been suggested by an increasing number of studies in recent years (42)(43)(44)(45). A number of studies have shown that cell wall invertases are sink tissue specifically expressed and up-regulated by stimuli that are associated with an increased demand for carbohydrates such as stress-related stimuli and growth-stimulating phytohormones (25). The specific involvement of invertases in anther development was suggested before for Lilium longiflorum (46,20), tomato (27), and potato (28).…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…This study strongly supports the importance of apoplastic cleavage of sucrose by extracellular invertase for supplying carbohydrates to sink tissues and for normal development of plants, which has been suggested by an increasing number of studies in recent years (42)(43)(44)(45). A number of studies have shown that cell wall invertases are sink tissue specifically expressed and up-regulated by stimuli that are associated with an increased demand for carbohydrates such as stress-related stimuli and growth-stimulating phytohormones (25). The specific involvement of invertases in anther development was suggested before for Lilium longiflorum (46,20), tomato (27), and potato (28).…”
Section: Discussionmentioning
confidence: 48%
“…Extracellular invertases of different species were shown to be encoded by small gene families with a differential regulation and expression pattern (25). Whereas most of the invertases characterized so far are not restricted to one specific plant organ, the extracellular invertase Nin88 of tobacco was shown to be characterized by a specific temporal and spatial expression pattern in anthers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to Hunter et al (1994) and Palliotti & Cartechini (2001), the hexoses (glucose and fructose) and the sucrose contents, as well as the activity of carbohydrate metabolizing enzymes in grapevine (Vitis vinifera L.) leaves, they are influenced by seasonal and phenological changes. Plant invertase gene expression and enzyme activity are both known to be influenced by a variety of intracellular and extra cellular factors (Tymowska-Lalanne & Kreis, 1998), such as environmental conditions, plant hormones and phenological stages (Roitsch et al, 2000(Roitsch et al, , 2003.…”
Section: Introductionmentioning
confidence: 99%
“…This property is commonly exploited in physiological studies aimed at better understanding of the regulatory roles and transport of sugars. Extracellular isomaltulose appears to be differentially sensed by plants (Loreti et al, 2000;Roitsch et al, 2000;Sinha et al, 2002;Atanassova et al, 2003), but known Suc transporters distinguish between isomers and do not detectably bind or transport isomaltulose (Li et al, 1994;Sivitz et al, 2007;Sun et al, 2010).…”
mentioning
confidence: 99%